Periodontal health, neutrophil activity and cardiovascular health in captive chimpanzees. (February 2022) - Raindi, Devan; Rees, Jacqueline; Hirschfeld, Josefine; Wright, Helen; Dobbs, Phillipa; Moittié, Sophie; White, Kate; Stahl, Wilhelm; Martin, Mike; Redrobe, Sharon; Hughes, Francis; Liptovszky, Matyas; et al.
Abstract: Objective: To investigate the association of dental and cardiac disease in a cohort of captive chimpanzees Design: 12 captive chimpanzees underwent periodontal and cardiac examinations under anaesthesia during a relocation to a new enclosure. Blood samples were taken for analysis of circulating markers of cardiac health, nutritional status and isolation of neutrophils for functional assays. They were then observed for three years for signs of heart disease. Results: Although the chimpanzees displayed large quantities of supragingival plaque, they had low bleeding scores. Peripheral blood neutrophils responded to innate and adaptive immune stimuli. In the follow up period two animals died and post mortem confirmed heart disease. Levels of NT-proBNP were found to be high in chimpanzees that died from heart disease. Conclusions: Whilst there appeared to be a correlation between probing depth and age, there appeared to be no correlation between dental data and heart data in this cohort. Highlights: Chimpanzees demonstrated generalised supragingival plaque and low bleeding score. Chimpanzee neutrophil function demonstrated similar responses to those reported from humans. High serum NT-proBNP levels were associated with later death from heart disease. Dental and cardiac data did not appear to correlate with each other.